The influence of environmental factors on pathogenesis of circulation system diseases – selected problems - Jerzemowski, Janusz (Studia Ecologiae et Bioethicae, 2009)
Environmental factors affect human organism in many ways. They can stabilize, modify or be the cause of many diseases, particularly of circulation system. Diseases of circulation system at the end of the last millennium in USA were the cause of 38% of all deaths. Such high degree of mortality causes necessity of undertaking prophylactic actions in order to reduce the negative influence of risk factors, particularly those environment factors which influence on pathogenesis of some diseases can be modified. Environment might be the factor which causes heart disease by: oxidation stress, inflammatory process, induction of coagulation system, dysfunction of autonomic system. Schetler (70) divided the factors favoring diseases of circulation system into two groups: risk factors (which have admitted participations in pathogenesis of heart and vascular diseases) and environmental factors which significance in pathogenesis of heart diseases still increases. It is commonly acknowledged that environmental factors which favor development of many diseases of circulation system belong to: physical factors polluting the air, water, soil and food, noise, electromagnetic field, ionizing radiation and electric energy. Most of them are industrial pollution – organic and non-organic. They include also six basic air pollution compounds (ozone, CO2, SO2, CO, PbO4, dust); chemical elements (Pb, Hg, Cd, CO, As, lack of Se); medicaments; alcohol and drug inducing stupor; smoking and passive smoking. Also malnutrition and low physical activity increase the risk of occurrence of many circulation system diseases. The described situation is magnified by the fact, that present civilization still increases the number of environmental factors negatively influencing heart-vascular system.